Immediate release tablets of Valsartan and Efavirenz: Role of concentration of superdisintegrants; [Comprimidos de liberación inmediata de Valsartán y Efavirenz: El papel de la concentración de superdisgregantes] - Kesavan K.; Rao U.V.; Bindu K.; Rajinikanth P.S.; Wani M.; Balasubramaniam J. (My University, 2025)
The objective of this study was to formulate directly compressible fast disintegrating tablets of poorly water soluble drugs with different extent of drug solubilities, like valsartan and efavirenz, as model drugs. Effect of varying concentrations of different superdisintegrants such as crospovidone, croscarmellose sodium, and sodium starch glycolate on disintegration time and in vitro drug dissolution was studied. The disintegration time of the best immediate release tablet formulation among those tested was observed to be 21.5±1.26 sec and 20.16±0.85 sec for valsartan and efavirenz tablets containing 20% of Crospovidone, respectively. Drug release (from both valsartan and Efavirenz tablets) was faster from formulations containing crospovidone compared to the other formulation. The effect was more apparent in Efavirenz, which has lesser aqueous solubility than valsartan. It was observed that 20% crospovidone was required to achieve 80% drug release from efavirenz tablets. Differential scanning calorimetric studies did not indicate any drug-excipient incompatibility. In conclusion, directly compressible fast disintegrating tablets of valsartan and efavirenz with shorter disintegration times and high dissolution rate were obtained and crospovidone seemed to be a better disintegrant for both valsartan and efavirenz, based on disintegration time and T80% values obtained.